Model Pentahelix dalam Pengembangan Desa Wisata di Desa Perlang Kabupaten Bangka Tengah, Bangka Belitung - Maulana, M; Hanafi, Syafiq Mahmadah; Azwar, Budi (Jurnal Magister Ekonomi Syariah, 2023)
In an effort to develop the Perlang Tourism Village, through the role of the Pentahelix Model. Perlang Tourism Village is one of the tourism areas located in Lubuk Besar District, Central Bangka Regency which has the potential to be developed because it has many attractive tourist destinations. The role of Pentahelix such as Academics, Business, Community, Government and Media seeks to develop Perlang Tourism Village for the better. However, it is not known in depth the involvement of related parties in the Development of the Perlang Tourism Village. Therefore, the researcher made the formulation of the problem in this research how is the Pentahelix Model in the development of the Perlang Tourism Village. The purpose of this study was to determine the involvement of the role of each informant to optimize the development potential of the Perlang Tourism Village. The method used in this research is descriptive qualitative. The conclusion in this study is that the Pentahelix Model in Perlang Tourism Village Development has been running optimally. This is because the collaboration between informants has been going well and the roles of each actor have been realized optimally.